2023
DOI: 10.1002/pc.27841
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric nanocomposite films based on anionic waterborne polyurethane and barium titanate nanoparticle: Fabrication, microstructure, and property characterization

Minyoung Seo,
Feng Tang,
Seok‐Ju Kim
et al.

Abstract: We report the fabrication, microstructure, thermal property, and piezoelectric performance of flexible waterborne polyurethane (WPU) nanocomposite films reinforced with barium titanate (BT) nanoparticles with ~50 nm diameter. An anionic segmented WPU was synthesized via bulk polymerization, and its nanocomposite films containing 10–40 wt% BT were fabricated via aqueous dispersion casting and hot pressing. Although the BT nanoparticles interacted with the urethane groups of the WPU hard segment by inducing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Due to the non‐availability of dielectric constant values for COPU/BTO composites, in our study we have compared experimentally evaluated results with piezoelectric polymer matrix composites, having BTO as inclusion and different non‐piezoelectric polymer as matrix phases. For example, Seo et al 70 also observed that the dielectric constant decreases with increasing frequency from 20 Hz to 2 MHz for neat water‐based polyurethane as well as polyurethane/BTO composites with BTO content in the range of 10 wt.% to 40 wt.%. This matches our experimental observation of monotonic decrease of dielectric constant as a function of frequency for all compositions of COPU/BTO composites studied in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the non‐availability of dielectric constant values for COPU/BTO composites, in our study we have compared experimentally evaluated results with piezoelectric polymer matrix composites, having BTO as inclusion and different non‐piezoelectric polymer as matrix phases. For example, Seo et al 70 also observed that the dielectric constant decreases with increasing frequency from 20 Hz to 2 MHz for neat water‐based polyurethane as well as polyurethane/BTO composites with BTO content in the range of 10 wt.% to 40 wt.%. This matches our experimental observation of monotonic decrease of dielectric constant as a function of frequency for all compositions of COPU/BTO composites studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…A direct comparison with existing literature is difficult because of the differences in experimental procedure as well as differences in the materials used and poling conditions used. For example, water‐soluble PU/40 wt.% BTO nanocomposite (with average BTO nanoparticle size of ~50 nm) has been reported to generate V OC and I SC values of ~0.51 V and ~ 43 nA under a compressive stress of 23 kPa 70 . The V OC reported by Seo et al 70 is close to the V OC value of 0.61 V obtained for CPBT‐5 (which has a comparable BTO microparticle content of ~38 wt.%) when it is subjected to a similar compressive stress of ~22 kPa; however, the I SC value of ~9 nA is significantly lower than that reported by Seo et al 70 …”
Section: Resultsmentioning
confidence: 99%
“…To assess the dispersion states of BT nanoparticles and BN nanosheets within the WPU matrix, SEM images of cross sections of the nanocomposite films with 40 wt % filler contents of different BT/BN ratios were obtained, as represented in Figure . For the nanocomposite film (WPU-T40) with only 40 wt % BT nanoparticles (Figure A), BT nanoparticles were agglomerated in the WPU matrix, which may be caused by high filler content and high density (∼6.02 g/cm 3 ) of BT nanoparticles during the aqueous dispersion casting. ,, It has been reported that the aggregation of BT nanoparticles within polymer matrices can be advantageous for enhancing piezoelectric performance . The reason is that when a compressional force is applied, the aggregated BT nanoparticles, which are also aligned by electric poling, induce a substantial dipole moment and thus lead to a significant potential difference.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of an anionic WPU and the fabrication of WPU aqueous dispersion were conducted through the procedure described in the previous article. , A series of WPU nanocomposite films, including BT and/or BT nanofillers, were manufactured via an efficient dispersion casting process, as schematically presented in Figure . An aqueous dispersion with 24 wt % WPU solid content was prepared by ultrasonication for 1 h. Predetermined amounts of BT nanoparticles and/or BN nanosheets were dispersed in DMF, which were then added into the WPU aqueous dispersion and ultrasonicated for 1 h. The mixed dispersion was applied onto a polypropylene plate and dried at 40 °C.…”
Section: Methodsmentioning
confidence: 99%